QUALITY OF LIFE AND EDUCATION FOR THE HEALTH: ANALYSIS OF THE PROFESSIONAL OF UNIVERSITY OF PHYSICAL EDUCATION OF SANTA CATARINA - BRAZIL (Fiep Bulletin - online, 2014)
The schools of Physical Education have modified its formatting constantly to take care of to the new requirements of market, if inserting in the form context to prepare apt professionals to execute the most diverse activities. Today, the resume of these courses is directed for a bigger approach of the health, in detriment of the sports, that were the main point of attention previously. A point, however, remains in open: although all the importance that the physical educator starts to have ahead of this new prism of the society, does not exist works that define which the profile of health and quality of life of this professional. In this direction, it is important to understand the reality of the professionals who act in these courses, its style of life and which the form with that they apply in its proper daily teachings that propagate in its lessons. This study it had as objective to verify the health and quality of life of the professional who acts in university, in the courses of Physical Education of the State of Santa Catarina - Brazil, in relation to the domain physical, psychological, social relation and environment. A census was become fullfilled where 132 participants had answered the shortened version Brazilian of the instrument of measure of quality of life and health of the OMS - Whoqol Bref. The gotten results had been of that in the physical domain they present good conditions in relation to the pain level, capacity for the work, rest and fatigue; in the social domain it has a significant number of unsatisfied people with the personal relations and the support received in the scopes familiar, professional and social; in the psychological domain they had presented optimism in relation to the life perspectives and in the capacity of concentration and learning; in the domain environment the answers demonstrate that necessities exist to supply in the fields financial, have carried and physical environment.
Keywords: Health; quality of life; professional of physical education